Scientific-Theoretical Psychological Analysis of Personal Activity Motivation - Sharafitdinov Abdulla XXX; Lutfullaeva Zumradoy Zokhidjon kizi; Djiyanova Billura Valijan kizi (Zien Journals, 2022)
The role and importance of motivation in personal activity is detailed in this article. A scientific theoretical psychological analysis of personal activity motivation was presented, and an attempt was made to reveal the essence of opinions and approaches expressed by our scientists through motivation theories
Keywords: Stable and unstable motivation; cognitive motivation; self-affirmation; identification